(untitled) (Al-Academy, 2015)
It seems that the features of the theatrical discourse , since its early establishment by the Greeks, were cultural features specifically confined to that society. Such features determined the direction of the theatrical discourse for this state instead of that state. There could be some sort of similarity among those features , nevertheless they remained within the general humanitarian framework . What achieved relatedness were those features and particularities that distinguished the theatrical community. Such features and particularities vary from one show to another. This is what we call " Local Specificity" .The Iraqi theatrical memory has always emphasized the concept of Experimentation through originality and renewal since the arrival of the European theatre and its invasion of the Iraqi community and through comprehending the experiments of the pioneers European experimentalists. Its chart varied according to the political and economic circumstances which the Iraqi community went through. In the beginning of the twentieth century and under the openness of the Iraqi community with all forms of communications with the others, and with the cultural and technological informational invasion of globalization , all this influenced those interested in theatrical movement forcing them either to duplicate or be original . Add to this the pursuance and the introduction of the latest artistic theatrical discourse to the Iraqi recipient .Accordingly , we can add the globalization awareness to the Iraqi theatrical discourse as something new that has an impact on the theatrical visual system ;hence the researcher has the significance of the present topic to deal with globalization and local identity.The present paper falls into the following sections: -The methodological framework which includes the problem, significance and aim of the research-. – The theoretical framework which includes two sections. The first is titled "The concept of globalization and the local culture". The second is titled " Manifestations of globalization in contemporary theatrical trends".The procedural steps include the methodology, research community, research sample, the tool. Analysis of the sample is represented by "AZEEZA" drama. The paper has arrived at the following findings :- culture did not affect the implications of the Iraqi theatrical discourse due to the fact that the reality of the Iraqi society includes various implications and richness that feed the Iraqi theatrical performance. – The visual system was affected by the variables imposed by globalization. Annexed to the paper are the references and an English abstract